2009
DOI: 10.1038/ijo.2009.180
|View full text |Cite
|
Sign up to set email alerts
|

Appropriate cutoff values of anthropometric variables to predict cardiovascular outcomes: 7.6 years follow-up in an Iranian population

Abstract: Objective: To determine cutoff points of anthropometric variables for predicting incident cardiovascular disease (CVD) in Iranian adults. Design: It is a population-based longitudinal study. Subjects: A total of 1614 men and 2006 women, aged X40 years, free of CVD at baseline were included in the study. Measurements: Body mass index (BMI), waist circumference (WC), waist-to-hip ratio (WHR), waist-to-height ratio (WHtR) and cardiovascular risks were assessed. Incident CVD was ascertained over a median of 7.6 ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
82
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(93 citation statements)
references
References 42 publications
(47 reference statements)
9
82
1
Order By: Relevance
“…According to our findings, remarkable portion of obesity effect appears to operate through the mediators (high excess risk), a phenomenon that has also been shown by other studies (18)(19)(20). Consequently, although fully adjusted models including mediators are subject to over-adjustment, proper cut-off points should not be determined without taking into account other metabolic risks.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…According to our findings, remarkable portion of obesity effect appears to operate through the mediators (high excess risk), a phenomenon that has also been shown by other studies (18)(19)(20). Consequently, although fully adjusted models including mediators are subject to over-adjustment, proper cut-off points should not be determined without taking into account other metabolic risks.…”
Section: Discussionsupporting
confidence: 68%
“…In Iran, two published cross-sectional studies resulted in contradictory findings regarding both values and gender differences that were 91.5/85.5 cm versus 89/91 cm in men/women (1; 23). The only report that was based on longitudinal data recommended 94.5 cm for both men and women (18). Based on these studies, the Ministry of Health in Iran has recently declared that the cut-off values for central obesity in men and women would be 95 cm for preventive purposes (6).…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have suggested that WC is a good indicator for predicting the risk of cardiovascular disease (28,29), while other studies have shown that waisthip ratio is a better indicator for predicting the risk of cardiovascular disease compared to WC and BMI (30). Yusuf and colleagues reported in their study that, waist-toheight ratio as an indicator of central obesity is a better predictor of cardiovascular events compared to WC and BMI in both sexes (31).…”
Section: Discussionmentioning
confidence: 98%
“…is not straightforward. In Tehran Lipid and Glucose Study, there was no difference between central obesity variables in predicting CVD in males, but in females WHpR and WHtR were better than WC and BMI [29]. In another paper from the same country, BMI or WHpR predicted the onset of diabetes mellitus after 3.6 years of follow-up in subjects aged less than 60 years.…”
Section: Which Anthropometric Index Is the Best?mentioning
confidence: 86%